Marine heatwaves reorganize phytoplankton bloom phenology in the Gulf of Alaska - Hisatomo Waga; Hiromichi Ueno; Thomas B. Kelly; Curry J. Cunningham; Sarah M. Hendricks (Limnology and Oceanography, 2026)
Phytoplankton blooms structure primary production and food‐web dynamics in the Gulf of Alaska, yet their response to recent warming and marine heatwaves (MHWs) remains poorly described. Using a parametric Gaussian framework applied to 21 years of satellite chlorophyll a (Chl a ), this study classified daily Chl a timeseries into double‐bloom, single spring‐bloom, single fall‐bloom, and no‐bloom regimes and related these to large‐scale oceanographic and atmospheric forcing. Double blooms with distinct spring and fall peaks dominated much of the domain in cold, dynamically active years characterized by negative sea surface temperature anomalies, depressed sea level, strong cross‐shelf pressure gradients, and more frequent storms associated with an intensified Aleutian Low. In contrast, warm years with elevated sea level and weaker cross‐shelf and atmospheric forcing favored single spring blooms and, in some areas, no‐bloom conditions, while single fall blooms occurred under intermediate physical states. Although no significant linear trends in the areal extent occupied by each regime were detected over 2003–2023, years influenced by major MHWs projected strongly onto the warm, weakly forced end of this physical gradient and were associated with reduced double‐bloom extent and an increased prevalence of single spring and no‐bloom regimes. These shifts imply that contraction and weakening of the seasonal production window, with likely consequences for zooplankton growth, match–mismatch dynamics for fish early life stages, and the balance between pelagic retention and export, highlighting how MHWs and ongoing climate change can suppress and reorganize phytoplankton bloom phenology in the Gulf of Alaska.

Revisiting evolutionary rescue in the wild - Laurinne J. Balstad; Marissa L. Baskett; Stephanie M. Carlson; Curry J. Cunningham; Peter A.H. Westley (Trends in Ecology & Evolution, 2026)

Control of fall armyworm with Spodoptera frugiperda multiple nucleopolyhedrovirus in sweet corn cultivated under agroecological conditions - T. Cunningham; C. de la Colina; M. Pérez; G. Quintana; Marco D´Amico; M. Berretta; J. Niz; M. L. Ferrelli; R. Salvador (BioControl, 2026)

Food variety affects food selection and variety-seeking behaviors in an immersive virtual reality food buffet - John W. Long; Paige M. Cunningham; Kathleen L. Keller; Barbara J. Rolls; Travis D. Masterson (Appetite, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Sensory-specific satiety and the influence of variety on snack intake in school-aged children - Paige M. Cunningham; Cara T. Meehan; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2026)

Beyond the Surface: Non-Invasive Low-Field NMR Analysis of Microbially-Induced Calcium Carbonate Precipitation in Shale Fractures - Matthew R. Willett; Kayla Bedey; Dustin Crandall; Joseph D. Seymour; Jonny Rutqvist; Alfred B. Cunningham; Adrienne J. Phillips; Catherine M. Kirkland (Rock Mechanics and Rock Engineering, 2026)
Microbially-induced calcium carbonate precipitation (MICP) is a biological process in which microbially-produced urease enzymes convert urea and calcium into solid calcium carbonate (CaCO 3 ) deposits. MICP has been demonstrated to reduce permeability in shale fractures under elevated pressures, raising the possibility of applying this technology to enhance shale reservoir storage safety. For this and other applications to become a reality, non-invasive tools are needed to determine how effectively MICP seals shale fractures at subsurface temperatures. In this study, two different MICP strategies were tested on 2.54 cm diameter and 5.08 cm long shale cores with a single fracture at 60 ℃. Flow-through, pulsed-flow MICP-treatment was repeatedly applied to Marcellus shale fractures with and without sand (“proppant”) until reaching approximately four orders of magnitude reduction in apparent permeability, while a single application of polymer-based “immersion” MICP-treatment was applied to an Eagle Ford shale fracture with proppant. Low-field nuclear magnetic resonance (LF-NMR) and X-Ray computed microtomography (micro-CT) techniques were used to assess the degree of biomineralization. With the flow-through approach, these tools revealed that while CaCO 3 precipitation occurred throughout the fracture, there was preferential precipitation around proppant. Without proppant, the same approach led to premature sealing at the inlet side of the core. In contrast, immersion MICP-treatment sealed off the fracture edges and showed less mineral precipitation overall. This study highlights the use of LF-NMR relaxometry in characterizing fracture sealing and can help guide NMR logging tools in subsurface remediation efforts.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

High satiety: Evaluating determinants of energy compensation and intake in multiple preloading studies - Barbara J. Rolls; Liane S. Roe; Paige M. Cunningham; Kathleen L. Keller; Faris M. Zuraikat (Appetite, 2025)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

The psychedelic (−)-2,5-dimethoxy-4-iodoamphetamine [(−)-DOI] demonstrates efficacy in reducing cocaine reward and motivation in male rats - Leah M. Salinsky; Christina R. Merritt; Erik J. Garcia; Robert G. Fox; Joshua C. Zamora; Noelle C. Anastasio; Kathryn A. Cunningham (Psychopharmacology, 2025)
Rationale and objectives Overdose fatalities involving cocaine continue to rise with over 5.3 million cocaine users reported in the United States in 2022. The abuse liability of cocaine is reliant upon inhibition of dopamine ( DA ) reuptake and consequent increase in DA efflux in meso-corticolimbic circuitry that controls reward and motivation. Cocaine also increases serotonin ( 5-HT ) efflux which is integral in cocaine abuse. The 5-HT 2A receptor ( 5-HT 2A R ) is a key regulator of meso-corticolimbic DA release and controls cellular mechanisms underlying cocaine effects. 5-HT 2A R actions contribute importantly to psychedelic mechanisms of action, and the efficacy of these compounds in limiting cocaine intake is unknown. The present studies evaluated the efficacy of acute administration of a psychedelic to reduce cocaine intake using standard and advanced preclinical models of drug self-administration. Methods Both a standard fixed ratio ( FR ) schedule and behavioral economics threshold procedure of cocaine intravenous self-administration were employed to evaluate the efficacy of the psychedelic 5-HT 2A R agonist (−)-2,5-dimethoxy-4-iodoamphetamine [ ( − )-DOI ] to decrease cocaine intake and motivation for cocaine in male rats. The 5-HT 2A R-selective antagonist M100907 was utilized to explore the role of 5-HT 2A R in the effects of (−)-DOI on cocaine intake. Results We found that (−)-DOI dose-dependently reduced intake on the FR5 schedule of cocaine IVSA and left shifted the demand curve to evoke greater sensitivity to price increases in the behavioral economics paradigm. Pretreatment with M100907 abated the efficacy of (−)-DOI on cocaine intake in both paradigms. Conclusion (−)-DOI ‘devalued’ cocaine reward and motivation to take cocaine in a 5-HT 2A R-dependent manner. As serotonergic psychedelics emerge as therapeutic candidates, investigations of 5-HT 2A R-acting psychedelics in preclinical analyses of cocaine intake and relapse vulnerability during abstinence will be valuable as prelude to future clinical trials.

Variety-seeking behavioral markers in an immersive virtual reality food buffet are associated with greater food and energy intake in laboratory meals - John W. Long; Paige M. Cunningham; Sara J. Maksi; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Janelle Kort; Paige Grabusky; Barbara J. Rolls; et al. (Appetite, 2025)

Escalating threats: house mouse attacks on adult wandering albatrosses spread across Marion Island - Michelle M. Risi; Christopher W. Jones; Maëlle Connan; Rhiannon Gill; Vanessa Stephen; Susan J. Cunningham; Peter G. Ryan (Biological Invasions, 2025)

Parasite induced changes in contact behaviour is affected by parasitic status of group members - Alex M. M. Morris; Giles T. Innocent; Emma J. A. Cunningham; Darren P. Croft; Spiridoula Athanasiadou; Michael R. Hutchings; Lesley A. Smith (Behavioral Ecology and Sociobiology, 2025)
Understanding how parasitism may affect social behavior and social networks is key to understanding the impact of infection on a population. Infection can disrupt social networks by altering the behavior of both infected individuals (e.g. by reducing activity) and the behavior of uninfected individuals (e.g. avoiding sick individuals), both of which can have an impact on social group dynamics and parasite transmission. Here we test experimentally how parasitism affects social contact behavior and social network structure using a common parasite infection of sheep. Three treatment groups, each with 4 replicate social groups were established (i) Parasitised; all lambs were infected with a parasitic nematode, (ii) Non-parasitised; all lambs remained uninfected (iii) Mixed; part of each group were infected, and part of the group remained uninfected. Contact behaviours of each individual were recorded using proximity loggers during four phases of infection (pre-parasite, pre-patent, patent-parasite, post-parasite). We found infected individuals in the parasitised and mixed groups reduced contact frequency following infection. Despite the reduction in contacts between infected animals in the mixed group, non-infected individual’s maintained pre-parasite levels of social interactions with their infected conspecifics. These results demonstrate how infection can impact the social behavior of all animals within a group, and how the expression of behavioral change may depend on the parasitic status of all group members and the response of uninfected conspecifics. Significance statement Parasitism is known to influence animal behavior and social interactions; however groups of animals will often contain individuals of different parasitic status. Understanding the behavioral response of both infected and uninfected members of a group is important to predict the consequences of infection throughout a population. We show, under experimental conditions, that parasitism not only reduces the frequency of contacts between infected lambs at the earliest stages of infection in both mixed and single-parasitic state groups, but also the degree of behavior change exhibited by infected animals is influenced by the parasitic status of other individuals within the group. We also show that although infected animals in mixed-state groups had reduced contact frequency with their infected groupmates, non-infected animal’s maintained pre-infection levels of social interactions.

Accumulation of benzotriazole UV-stabilizers in relation to ingested plastics and associated health metrics in Larus gulls feeding at a landfill in Atlantic Canada - Kerry Schutten; André Morrill; Zhe Lu; Akshaya Chandrashekar; Joshua T. Cunningham; Gregory J. Robertson; Mark L. Mallory; Claire M. Jardine; Jennifer F. Provencher (Journal of Hazardous Materials, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Connectivity Benefits Most Woodland Invertebrate Species but Only in Landscapes With Low Woodland Cover - Charles A. Cunningham; Colin M. Beale; Diana E. Bowler; Michael J. O. Pocock; Robin Hutchinson; Piran C. L. White; Merryn Hunt; Lindsay Maskell; Jane K. Hill (Ecology Letters, 2025)
Connectivity is widely assumed to benefit biodiversity, but this has not been extensively quantified across multiple taxa and landscapes. Focusing on the UK, where woodland cover is low (13%), we analysed species occurrence records from citizen science for over 800 broadleaf woodland‐associated invertebrate species from 15 taxonomic groups in relation to woodland cover and connectivity. Overall, increased woodland connectivity positively affects broadleaf‐associated species occurrence (effect of connectivity across species, accounting for positive effect of broadleaf cover). The benefits of connectivity varied considerably by species: 39% of species showed a significant positive effect, while for 3% it was significantly negative. However, the interaction between cover and connectivity revealed that, overall, connectivity benefits are only found in low cover landscapes. Our findings emphasise potential biodiversity benefits from maximising connectivity when increasing woodland cover and highlight the importance of spatial targeting in restoration efforts, especially in landscapes with low woodland cover.

Navigating the risks and rewards of scavenging in multipredator, human‐impacted landscapes - Calum X. Cunningham; Rebecca Windell; Lauren C. Satterfield; Aaron J. Wirsing; Thomas M. Newsome; Taylor R. Ganz; Laura R. Prugh (Ecology, 2025)
Large carnivores can influence smaller scavengers through both positive and negative interactions (e.g., carrion provisioning and intraguild killing) and ultimately shape scavenging efficiency. However, we know little about this trade‐off in anthropogenic landscapes where humans kill carnivores and provide carrion subsidies. In the context of wolf ( Canis lupus ) recolonization of human‐impacted landscapes in Washington, USA, we investigated how sources of ungulate mortality (wolves, cougars [ Puma concolor ], and vehicles) shape scavenging efficiency, community‐wide carcass visitations, and the strategies used by scavengers to navigate risk–reward trade‐offs. Cougar and wolf kills mostly occurred in areas with low‐to‐moderate human influence, whereas roadkill typically occurred in areas with high human impact. Wolves consumed their kills most rapidly (median Cathartes aura ) and black bears ( Ursus americanus ), which are obligate and apex scavengers, respectively, coincided with a seasonal increase in scavenging by most other species. The two mammalian mesocarnivores exhibited divergent strategies: Coyotes ( Canis latrans ) frequently scavenged but usually for short durations and with heightened vigilance at predator kills, whereas bobcats ( Lynx rufus ) visited carcasses less frequently but fed for longer durations and displayed low vigilance while scavenging. These results suggest a hierarchical decision‐making process whereby scavengers first choose whether to forage at a carcass before fine‐tuning foraging duration, using temporal refugia, or increasing vigilance. Predator recovery in human‐dominated landscapes therefore adds complexity to the spatiotemporal landscape of risks and rewards, and outcomes for scavengers will likely depend on their propensity to scavenge and vulnerability to humans and large predators.

Food switching at a meal is positively associated with change in adiposity among children at high-familial risk for obesity - Nicholas V. Neuwald; Alaina L. Pearce; Paige M. Cunningham; Marissa N. Setzenfand; Lauren Koczwara; Barbara J. Rolls; Kathleen L. Keller (Appetite, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

An interdisciplinary approach to improving conservation outcomes for parasites - Timothy M. Brown; Alison M. Dunn; Rupert J. Quinnell; Ellen Clarke; Andrew A. Cunningham; Simon J. Goodman (Conservation Biology, 2025)
Parasites represent a significant proportion of Earth's biodiversity and play important roles in the ecology and biology of ecosystems and hosts, making them an important target for conservation. Despite increasing calls to prioritize protection for parasites in the academic literature, they remain undervalued and underrepresented in global biodiversity conservation efforts, not least due to the perception that the interests of parasite and host conservation are opposing and the common misconception that parasites are a threat, rather than a benefit, to conservation. We considered whether taking an interdisciplinary approach to parasite conservation research will generate novel insights and solutions concerning why and how parasite conservation should be practiced for the benefit of parasites, their hosts, ecosystems, and people. We argue that 2 of the main barriers to more widespread parasite conservation are the knowledge gap concerning the role of sociocultural factors affecting the willingness to enact parasite conservation and the lack of a consistent and cohesive philosophical basis for parasite conservation. Possible sociocultural barriers to parasite conservation include misconceptions of the risks posed by parasites, taxonomic bias, differences in conservation values, economic constraints, and technical challenges. The use of social science can generate insights into levels of awareness and support for parasite conservation and improve understanding of how human values and attitudes mediate conservation practices concerning parasites. Such knowledge will have a critical role in addressing sociocultural barriers and improving support for parasite conservation. Issues with the current philosophical basis for parasite conservation include contradictory accounts of which parasites merit conservation, insufficient explanation of how different conservation values apply to parasite biodiversity, and the existence of a false antagonism between host and parasite conservation. Greater engagement with philosophical work on environmental ethics and biological unitization will strengthen existing arguments for parasite conservation and will support conservation decision‐making processes.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Formation of vertical columnar seismic structures and seafloor depressions by groundwater discharge in the drowned Miami Terrace platform and overlying deep-water carbonates, southeastern Florida - Kevin J. Cunningham; Richard L. Westcott; Sean Norgard; Edward Robinson; Harry J. Dowsett; Marci M. Robinson (Marine Geology, 2024)

The BirdLife Seabird Tracking Database: 20 years of collaboration for marine conservation - Ana P.B. Carneiro; Maria P. Dias; Bethany L. Clark; Elizabeth J. Pearmain; Jonathan Handley; Amy R. Hodgson; John P. Croxall; Richard A. Phillips; Steffen Oppel; Joanne M. Morten; Ben Lascelles; Cleo Cunningham; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Body size and early marine conditions drive changes in Chinook salmon productivity across northern latitude ecosystems - Megan L. Feddern; Rebecca Shaftel; Erik R. Schoen; Curry J. Cunningham; Brendan M. Connors; Benjamin A. Staton; Al von Finster; Zachary Liller; Vanessa R. von Biela; Katherine G. Howard (Global Change Biology, 2024)
Disentangling the influences of climate change from other stressors affecting the population dynamics of aquatic species is particularly pressing for northern latitude ecosystems, where climate‐driven warming is occurring faster than the global average. Chinook salmon ( Oncorhynchus tshawytscha ) in the Yukon‐Kuskokwim (YK) region occupy the northern extent of their species' range and are experiencing prolonged declines in abundance resulting in fisheries closures and impacts to the well‐being of Indigenous people and local communities. These declines have been associated with physical (e.g., temperature, streamflow) and biological (e.g., body size, competition) conditions, but uncertainty remains about the relative influence of these drivers on productivity across populations and how salmon–environment relationships vary across watersheds. To fill these knowledge gaps, we estimated the effects of marine and freshwater environmental indicators, body size, and indices of competition, on the productivity (adult returns‐per‐spawner) of 26 Chinook salmon populations in the YK region using a Bayesian hierarchical stock‐recruitment model. Across most populations, productivity declined with smaller spawner body size and sea surface temperatures that were colder in the winter and warmer in the summer during the first year at sea. Decreased productivity was also associated with above average fall maximum daily streamflow, increased sea ice cover prior to juvenile outmigration, and abundance of marine competitors, but the strength of these effects varied among populations. Maximum daily stream temperature during spawning migration had a nonlinear relationship with productivity, with reduced productivity in years when temperatures exceeded thresholds in main stem rivers. These results demonstrate for the first time that well‐documented declines in body size of YK Chinook salmon were associated with declining population productivity, while taking climate into account.

An economic indicator of the orbital debris environment - Nodir Adilov; Peter J. Alexander; Vitali Braun; Brendan M. Cunningham (Journal of Space Safety Engineering, 2024)

Temporal dynamics of Devonian reef communities: Insights into natural phase shifts and long-term resilience in the face of environmental variability - Amanda Godbold; Nina Clark; Emer T. Cunningham; David J. Bottjer; John M. Pandolfi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Intensive professional vehicle-based shooting provides local control of invasive rusa deer in a peri-urban landscape - Sebastien Comte; Andrew J. Bengsen; Calum X. Cunningham; Michelle Dawson; Anthony R. Pople; David M. Forsyth (Biological Invasions, 2024)
Non-native deer are becoming increasingly common in peri-urban landscapes, where they pose a risk to the health and wellbeing of people. Professional vehicle-based shooting is commonly used to control deer populations in these complex landscapes, but the effectiveness and cost of this method have seldom been evaluated. We analyzed the effectiveness and cost of using professional vehicle-based shooting to reduce the abundance and impacts of non-native rusa deer ( Cervus timorensis ) in a peri-urban landscape in Wollongong, eastern Australia, during 2011–2021. We incorporated the results from an independent monitoring program into a Bayesian joint-likelihood framework to model spatio-temporal changes in rusa deer abundance. Finally, we used our findings to assess the effect of the management program on the number of complaints from the residents. After eleven years and the removal of 4701 rusa deer from Wollongong LGA (712 km 2 ), deer abundance did not change in 74.7% of the area, decreased in 19.4% of the area (mostly in and around the sites where the professional shooting occurred), and increased in 5.9% of the area. Shooting was most cost-effective during winter when the longer hours of darkness meant that shooters could visit more sites. In contrast to deer abundance, the probability of residents complaining about deer increased in space and time. Our study shows that professional vehicle-based shooting can locally reduce the abundance of invasive deer in a peri-urban landscape, providing that sufficient control effort is expended. We suggest that shooting effort is currently too thinly spread across this peri-urban landscape, and that concentrating shooting effort on the areas of greatest deer abundance and resident complaints might be a more cost-effective strategy for managing invasive deer in peri-urban landscapes.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Pacific salmon in the Canadian Arctic highlight a range‐expansion pathway for sub‐Arctic fishes - Karen M. Dunmall; Joseph A. Langan; Curry J. Cunningham; James D. Reist; Humfrey Melling (Global Change Biology, 2024)
Rapid climate change is altering Arctic ecosystems at unprecedented rates. These changes in the physical environment may open new corridors for species range expansions, with substantial implications for subsistence‐dependent communities and sensitive ecosystems. Over the past 20 years, rising incidental harvest of Pacific salmon by subsistence fishers has been monitored across a widening range spanning multiple land claim jurisdictions in Arctic Canada. In this study, we connect Indigenous and scientific knowledges to explore potential oceanographic mechanisms facilitating this ongoing northward expansion of Pacific salmon into the western Canadian Arctic. A regression analysis was used to reveal and characterize a two‐part mechanism related to thermal and sea‐ice conditions in the Chukchi and Beaufort seas that explains nearly all of the variation in the relative abundance of salmon observed within this region. The results indicate that warmer late‐spring temperatures in a Chukchi Sea watch‐zone and persistent, suitable summer thermal conditions in a Beaufort Sea watch‐zone together create a range‐expansion corridor and are associated with higher salmon occurrences in subsistence harvests. Furthermore, there is a body of knowledge to suggest that these conditions, and consequently the presence and abundance of Pacific salmon, will become more persistent in the coming decades. Our collaborative approach positions us to document, explore, and explain mechanisms driving changes in fish biodiversity that have the potential to, or are already affecting, Indigenous rights‐holders in a rapidly warming Arctic.

Poorer inhibitory control was related to greater food intake across meals varying in portion size: A randomized crossover trial - Paige M. Cunningham; Liane S. Roe; Alaina L. Pearce; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2024)

Reasons for meal termination, eating frequency, and typical meal context differ between persons with and without a spinal cord injury - Gary J. Farkas; Paige M. Cunningham; Alicia M. Sneij; John E. Hayes; Mark S. Nash; Arthur S. Berg; David R. Gater; Barbara J. Rolls (Appetite, 2024)

Pyrogeography in flux: Reorganization of Australian fire regimes in a hotter world - Calum X. Cunningham; Grant J. Williamson; Rachael H. Nolan; Lina Teckentrup; Matthias M. Boer; David M. J. S. Bowman (Global Change Biology, 2024)
Changes to the spatiotemporal patterns of wildfire are having profound implications for ecosystems and society globally, but we have limited understanding of the extent to which fire regimes will reorganize in a warming world. While predicting regime shifts remains challenging because of complex climate–vegetation–fire feedbacks, understanding the climate niches of fire regimes provides a simple way to identify locations most at risk of regime change. Using globally available satellite datasets, we constructed 14 metrics describing the spatiotemporal dimensions of fire and then delineated Australia's pyroregions—the geographic area encapsulating a broad fire regime. Cluster analysis revealed 18 pyroregions, notably including the (1) high‐intensity, infrequent fires of the temperate forests, (2) high‐frequency, smaller fires of the tropical savanna, and (3) low‐intensity, diurnal, human‐engineered fires of the agricultural zones. To inform the risk of regime shifts, we identified locations where the climate under three CMIP6 scenarios is projected to shift (i) beyond each pyroregion's historical climate niche, and (ii) into climate space that is novel to the Australian continent. Under middle‐of‐the‐road climate projections (SSP2‐4.5), an average of 65% of the extent of the pyroregions occurred beyond their historical climate niches by 2081–2100. Further, 52% of pyroregion extents, on average, were projected to occur in climate space without present‐day analogues on the Australian continent, implying high risk of shifting to states that also lack present‐day counterparts. Pyroregions in tropical and hot‐arid climates were most at risk of shifting into both locally and continentally novel climate space because (i) their niches are narrower than southern temperate pyroregions, and (ii) their already‐hot climates lead to earlier departure from present‐day climate space. Such a shift implies widespread risk of regime shifts and the emergence of no‐analogue fire regimes. Our approach can be applied to other regions to assess vulnerability to rapid fire regime change.

First report of Ornithogalum virus 3 in Galtonia candicans in the United Kingdom - J Dixon; K Chisnall; M Mynett; C Cunningham; G Webster; A Skelton; A. R. Fowkes; A Fox (Journal of Plant Pathology, 2023)

Variety and portion size combine to increase food intake at single-course and multi-course meals - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2023)

Occurrence and sources of microplastics on Arctic beaches: Svalbard - Tesni Lloyd-Jones; Jonathan J. Dick; Timothy P. Lane; Eoghan M. Cunningham; Konstadinos Kiriakoulakis (Marine Pollution Bulletin, 2023)

Revising vulnerability assessments of montane birds in the colombian páramo to account for threats from climate change - Christopher J Wheatley; Colin M Beale; Piran C L White; Adrián Villaseñor; Adriana Sanchez; Charles A Cunningham; Jane K Hill (Biodiversity and Conservation, 2023)
Tropical montane ecosystems are highly vulnerable to global climate change, but their species-level conservation vulnerability assessments generally do not incorporate climate threats. The Colombian páramo is a highly diverse montane ecosystem but it contains relatively few species currently identified as threatened on the IUCN Red List. We explore whether current assessments need revising to account for climate change threats for páramo species. We use a climate change vulnerability assessment framework to evaluate the risks and opportunities from climate change for 60 bird species within the Colombian páramo. We explore two potential climate change scenarios (RCP 2.6 and RCP 8.5), representing best and worst-case projections. We find that more than half (52–68%, depending on the scenario) of bird species will be threatened by climate change by the end of the century, but a very poor agreement between the current conservation status of species and their climate vulnerability score. We find ~ 90% of species identified as climate-threatened are not currently identified as being of conservation concern, representing a substantial new suite of priority species within the Colombian páramo. Overall, we identify up to 34 páramo bird species that are threatened by climate change but not currently listed as being of conservation concern. Similar mismatches may also occur in other montane taxa and so updating species risk assessments to account for climate change is urgently needed. Implementation of appropriate conservation actions is also needed to reduce species’ risks from climate change.

A zero-dose vulnerability index for equity assessment and spatial prioritization in low- and middle-income countries - C.E. Utazi; H.M.T. Chan; I. Olowe; A. Wigley; N. Tejedor-Garavito; A. Cunningham; M. Bondarenko; J. Lorin; D. Boyda; D. Hogan; A.J. Tatem (Spatial Statistics, 2023)

Intersex manifestation in the rainbow darter (Etheostoma caeruleum): Are adult male fish susceptible to developing and recovering from intersex after exposure to endocrine active compounds? - Keegan A. Hicks; Meghan L.M. Fuzzen; Hadi A. Dhiyebi; Leslie M. Bragg; Patricija Marjan; Jessie Cunningham; Mark E. McMaster; Nivetha Srikanthan; Kirsten E. Nikel; Maricor J. Arlos; Mark R. Servos (Aquatic Toxicology, 2023)

The role of Dnmt1 in oocyte development - Emily A. Shelby; Elizabeth C. McKinney; Christopher B. Cunningham; Alvin M. Simmons; Allen J. Moore; Patricia J. Moore (Journal of Insect Physiology, 2023)

Switching between bites of food and sips of water is related to food intake across meals varying in portion size - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2023)

Research needs, environmental concerns, and logistical considerations for incorporating livestock grazing into coastal upland habitat management - K. Gill; K.A. Chenier; A. Free; J. Goff; J.L. Pitchford; K. Cressman; M. Posten; E. Brunden; M. Shelton; K. Swanson; S.R. Cunningham; J. Garland; et al. (Journal of Environmental Management, 2023)

Time-varying effects of local weather on behavior and probability of breeding deferral in two Arctic-nesting goose populations - Stephanie A. Cunningham; Toryn L. J. Schafer; Christopher K. Wikle; Jay A. VonBank; Bart M. Ballard; Lei Cao; Stuart Bearhop; Anthony D. Fox; Geoff M. Hilton; Alyn J. Walsh; Larry R. Griffin; Mitch D. Weegman (Oecologia, 2023)
Arctic-nesting geese face energetic challenges during spring migration, including ecological barriers and weather conditions (e.g., precipitation and temperature), which in long-lived species can lead to a trade-off to defer reproduction in favor of greater survival. We used GPS location and acceleration data collected from 35 greater white-fronted geese of the North American midcontinent and Greenland populations at spring migration stopovers, and novel applications of Bayesian dynamic linear models to test daily effects of minimum temperature and precipitation on energy expenditure (i.e., overall dynamic body acceleration, ODBA) and proportion of time spent feeding (PTF), then examined the daily and additive importance of ODBA and PTF on probability of breeding deferral using stochastic antecedent models. We expected distinct responses in behavior and probability of breeding deferral between and within populations due to differences in stopover area availability. Time-varying coefficients of weather conditions were variable between ODBA and PTF, and often did not show consistent patterns among birds, indicating plasticity in how individuals respond to conditions. An increase in antecedent ODBA was associated with a slightly increased probability of deferral in midcontinent geese but not Greenland geese. Probability of deferral decreased with increased PTF in both populations. We did not detect any differentially important time periods. These results suggest either that movements and behavior throughout spring migration do not explain breeding deferral or that ecological linkages between bird decisions during spring and subsequent breeding deferral were different between populations and across migration but occurred at different time scales than those we examined.

Eating rate and bite size were related to food intake across meals varying in portion size: A randomized crossover trial in adults - Paige M. Cunningham; Liane S. Roe; Kathleen L. Keller; Anouk E.M. Hendriks-Hartensveld; Barbara J. Rolls (Appetite, 2023)

Correction to: Childhood blood lead levels and environmental risk factors in Madagascar - Wyatt M. Champion; Adaline M. Buerck; Christopher Nenninger; Korede Yusuf; Luke J. P. Barrett; Lova Rakotoarisoa; Rinah Rakotondrazaka; Katherine Alfredo; Jeffrey Cunningham; Mahmooda Khaliq; James R. Mihelcic (Environmental Science and Pollution Research, 2022)

Childhood blood lead levels and environmental risk factors in Madagascar - Wyatt M. Champion; Adaline M. Buerck; Christopher Nenninger; Korede Yusuf; Luke J. P. Barrett; Lova Rakotoarisoa; Rinah Rakotondrazaka; Katherine Alfredo; Jeffrey Cunningham; Mahmooda Khaliq; James R. Mihelcic (Environmental Science and Pollution Research, 2022)

Mitogenomics reveals low variation within a trigeneric complex of black corals from the North Pacific Ocean - Yessenia M. Bledsoe-Becerra; Iesha S. Whittaker; Jeremy Horowitz; Katherine Medina Naranjo; Jicayla Johnson-Rosemond; Kristen H. Mullins; Karena M. Cunningham; Suchir Shetty; Samuel N. Messinides; Melinda S. Behney; Jessica A. Fehsal; Ashley N. Watson; et al. (Organisms Diversity & Evolution, 2022)

Starch Products as Candidate Excipients in a Continuous Direct Compression Line - Sonia M. Razavi; Yi Tao; James Scicolone; Tami Morker; Charles Cunningham; Ali Rajabi-Siahboomi; Douglas B. Hausner; Fernando J. Muzzio (Journal of Pharmaceutical Innovation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Multi-taxa spatial conservation planning reveals similar priorities between taxa and improved protected area representation with climate change - Rob Critchlow; Charles A. Cunningham; Humphrey Q. P. Crick; Nicholas A. Macgregor; Michael D. Morecroft; James W. Pearce-Higgins; Tom H. Oliver; Matthew J. Carroll; Colin M. Beale (Biodiversity and Conservation, 2022)
Protected area (PA) networks have in the past been constructed to include all major habitats, but have often been developed through consideration of only a few indicator taxa or across restricted areas, and rarely account for global climate change. Systematic conservation planning (SCP) aims to improve the efficiency of biodiversity conservation, particularly when addressing internationally agreed protection targets. We apply SCP in Great Britain (GB) using the widest taxonomic coverage to date (4,447 species), compare spatial prioritisation results across 18 taxa and use projected future (2080) distributions to assess the potential impact of climate change on PA network effectiveness. Priority conservation areas were similar among multiple taxa, despite considerable differences in spatial species richness patterns; thus systematic prioritisations based on indicator taxa for which data are widely available are still useful for conservation planning. We found that increasing the number of protected hectads by 2% (to reach the 2020 17% Aichi target) could have a disproportionate positive effect on species protected, with an increase of up to 17% for some taxa. The PA network in GB currently under-represents priority species but, if the potential future distributions under climate change are realised, the proportion of species distributions protected by the current PA network may increase, because many PAs are in northern and higher altitude areas. Optimal locations for new PAs are particularly concentrated in southern and upland areas of GB. This application of SCP shows how a small addition to an existing PA network could have disproportionate benefits for species conservation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

A novel knockout mouse for the small EDRK-rich factor 2 (Serf2) showing developmental and other deficits - Karen Cleverley; Weaverly Colleen Lee; Paige Mumford; Toby Collins; Matthew Rickman; Thomas J. Cunningham; James Cleak; Joffrey Mianne; Zsombor Szoke-Kovacs; Michelle Stewart; Lydia Teboul; Cheryl Maduro; et al. (Mammalian Genome, 2021)
The small EDRK-rich factor 2 (SERF2) is a highly conserved protein that modifies amyloid fibre assembly in vitro and promotes protein misfolding. However, the role of SERF2 in regulating age-related proteotoxicity remains largely unexplored due to a lack of in vivo models. Here, we report the generation of Serf2 knockout mice using an ES cell targeting approach, with Serf2 knockout alleles being bred onto different defined genetic backgrounds. We highlight phenotyping data from heterozygous Serf2 +/− mice, including unexpected male-specific phenotypes in startle response and pre-pulse inhibition. We report embryonic lethality in Serf2 −/− null animals when bred onto a C57BL/6 N background. However, homozygous null animals were viable on a mixed genetic background and, remarkably, developed without obvious abnormalities. The Serf2 knockout mice provide a powerful tool to further investigate the role of SERF2 protein in previously unexplored pathophysiological pathways in the context of a whole organism.

Cephalopods habitat and trophic ecology: historical data using snares penguin as biological sampler - H. R. Guímaro; D. R. Thompson; V. H. Paiva; F. R. Ceia; D. M. Cunningham; P. J. Moors; J. C. Xavier (Polar Biology, 2021)

Stroke Induces Prolonged Changes in Lipid Metabolism, the Liver and Body Composition in Mice - Michael J. Haley; Claire S. White; Daisy Roberts; Kelly O’Toole; Catriona J. Cunningham; Jack Rivers-Auty; Conor O’Boyle; Conor Lane; Oliver Heaney; Stuart M. Allan; Catherine B. Lawrence (Translational Stroke Research, 2020)
During recovery, stroke patients are at risk of developing long-term complications that impact quality of life, including changes in body weight and composition, depression and anxiety, as well as an increased risk of subsequent vascular events. The aetiologies and time-course of these post-stroke complications have not been extensively studied and are poorly understood. Therefore, we assessed long-term changes in body composition, metabolic markers and behaviour after middle cerebral artery occlusion in mice. These outcomes were also studied in the context of obesity, a common stroke co-morbidity proposed to protect against post-stroke weight loss in patients. We found that stroke induced long-term changes in body composition, characterised by a sustained loss of fat mass with a recovery of lean weight loss. These global changes in response to stroke were accompanied by an altered lipid profile (increased plasma free fatty acids and triglycerides) and increased adipokine release at 60 days. After stroke, the liver also showed histological changes indicative of liver damage and a decrease in plasma alanine aminotransferase (ALT) was observed. Stroke induced depression and anxiety-like behaviours in mice, illustrated by deficits in exploration, nest building and burrowing behaviours. When initial infarct volumes were matched between mice with and without comorbid obesity, these outcomes were not drastically altered. Overall, we found that stroke induced long-term changes in depressive/anxiety-like behaviours, and changes in plasma lipids, adipokines and the liver that may impact negatively on future vascular health.

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Floral resources of an invasive shrub alter native bee communities at different vertical strata in forest-edge habitat - M. J. Cunningham-Minnick; T. O. Crist (Biological Invasions, 2020)

High temperatures are associated with substantial reductions in breeding success and offspring quality in an arid-zone bird - T. M. F. N. van de Ven; A. E. McKechnie; S. Er; S. J. Cunningham (Oecologia, 2020)

Better off dead: assessment of aquatic disinfectants and thermal shock treatments to prevent the spread of invasive freshwater bivalves - Neil E. Coughlan; Stephanie J. Bradbeer; Ross N. Cuthbert; Eoghan M. Cunningham; Kate Crane; Stephen Potts; Joe M. Caffrey; Frances E. Lucy; Alison M. Dunn; Eithne Davis; Trevor Renals; Claire Quinn; et al. (Wetlands Ecology and Management, 2020)
Biosecurity protocols designed to prevent further spread of invasive alien species have become a key component of invader management strategies. Yet, the species-specific efficacy of many biosecurity treatments are frequently unclear or unknown. Invasive quagga, Dreissena bugensis , and zebra mussels, D. polymorpha , are a serious threat to freshwater ecosystems worldwide. Here, we examine the effectiveness of immersion (≤ 90 min) within 2% or 4% solutions for two commonly used disinfectants (Virasure® Aquatic and Virkon® Aquatic) to cause mortality of adult Dreissena bivalves . Further, we assessed the effectiveness of thermal treatments: steam spray (≥ 100 °C; ≤ 120 s); hot air (− 500 °C; ≤ 60 s); and dry ice exposure (− 78 °C; ≤ 300 g; 15 min). Complete mortality of D. polymorpha was observed following exposure to both disinfectants for 90 min, at both concentrations. However, high but incomplete mortality (40–90%) was recorded for D. bugensis across disinfectant treatments. For both species, complete mortality was achieved following 30 s of steam. In addition, 10 s of hot air and 15 min exposure to 300 g of dry ice can both completely killed groups of D. polymorpha . Overall, although the disinfectants did not cause complete mortality, it appears that relatively brief exposure to thermal treatments could be used to curtail the further spread of Dreissena species.

The costs of keeping cool: behavioural trade-offs between foraging and thermoregulation are associated with significant mass losses in an arid-zone bird - T. M. F. N. van de Ven; A. E. McKechnie; S. J. Cunningham (Oecologia, 2019)

Uses for humanised mouse models in precision medicine for neurodegenerative disease - Remya R. Nair; Silvia Corrochano; Samanta Gasco; Charlotte Tibbit; David Thompson; Cheryl Maduro; Zeinab Ali; Pietro Fratta; Abraham Acevedo Arozena; Thomas J. Cunningham; Elizabeth M. C. Fisher (Mammalian Genome, 2019)
Neurodegenerative disease encompasses a wide range of disorders afflicting the central and peripheral nervous systems and is a major unmet biomedical need of our time. There are very limited treatments, and no cures, for most of these diseases, including Alzheimer’s Disease, Parkinson's Disease, Huntington Disease, and Motor Neuron Diseases. Mouse and other animal models provide hope by analysing them to understand pathogenic mechanisms, to identify drug targets, and to develop gene therapies and stem cell therapies. However, despite many decades of research, virtually no new treatments have reached the clinic. Increasingly, it is apparent that human heterogeneity within clinically defined neurodegenerative disorders, and between patients with the same genetic mutations, significantly impacts disease presentation and, potentially, therapeutic efficacy. Therefore, stratifying patients according to genetics, lifestyle, disease presentation, ethnicity, and other parameters may hold the key to bringing effective therapies from the bench to the clinic. Here, we discuss genetic and cellular humanised mouse models, and how they help in defining the genetic and environmental parameters associated with neurodegenerative disease, and so help in developing effective precision medicine strategies for future healthcare.

Effects of historic and projected climate change on the range and impacts of an emerging wildlife disease - Stephen J. Price; William T. M. Leung; Christopher J. Owen; Robert Puschendorf; Chris Sergeant; Andrew A. Cunningham; Francois Balloux; Trenton W. J. Garner; Richard A. Nichols (Global Change Biology, 2019)
The global trend of increasing environmental temperatures is often predicted to result in more severe disease epidemics. However, unambiguous evidence that temperature is a driver of epidemics is largely lacking, because it is demanding to demonstrate its role among the complex interactions between hosts, pathogens, and their shared environment. Here, we apply a three‐pronged approach to understand the effects of temperature on ranavirus epidemics in UK common frogs, combining in vitro, in vivo, and field studies. Each approach suggests that higher temperatures drive increasing severity of epidemics. In wild populations, ranavirosis incidents were more frequent and more severe at higher temperatures, and their frequency increased through a period of historic warming in the 1990s. Laboratory experiments using cell culture and whole animal models showed that higher temperature increased ranavirus propagation, disease incidence, and mortality rate. These results, combined with climate projections, predict severe ranavirosis outbreaks will occur over wider areas and an extended season, possibly affecting larval recruitment. Since ranaviruses affect a variety of ectothermic hosts (amphibians, reptiles, and fish), wider ecological damage could occur. Our three complementary lines of evidence present a clear case for direct environmental modulation of these epidemics and suggest management options to protect species from disease.

Modeling the Effect of TNF-α upon Drug-Induced Toxicity in Human, Tissue-Engineered Myobundles - Brittany N. J. Davis; Jeffrey W. Santoso; Michaela J. Walker; Catherine E. Oliver; Michael M. Cunningham; Christian A. Boehm; Danielle Dawes; Samantha L. Lasater; Kim Huffman; William E. Kraus; George A. Truskey (Annals of Biomedical Engineering, 2019)

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Real-Time Monitoring with a Tablet App Improves Implementation of Treatments to Enhance Forest Structural Diversity - Colin T Maher; Emily Oja; Abigail Marshall; Matthew Cunningham; Lucas Townsend; Graham Worley-Hood; Luke Ruffner Robinson; Taylor Margot; Drew Lyons; Stuart Fety; Eryn E Schneider; Sean M A Jeronimo; et al. (Journal of Forestry, 2019)

Eastern rockhopper penguins Eudyptes filholi as biological samplers of juvenile and sub-adult cephalopods around Campbell Island, New Zealand - J. C. Xavier; Y. Cherel; F. R. Ceia; J. P. Queirós; B. Guimarães; R. Rosa; D. M. Cunningham; P. J. Moors; D. R. Thompson (Polar Biology, 2018)

Frequency, duration and severity of drought in the Semiarid Northeast Brazil region - S. S. B. Brito; A. P. M. A. Cunha; C. C. Cunningham; R. C. Alvalá; J. A. Marengo; M. A. Carvalho (International Journal of Climatology, 2018)
Drought is the natural disaster that impacts the greatest number of people and produces the most significant economic losses. This work presents a quantitative assessment of drought events occurred in the Semiarid region of Northeast Brazil during 1981–2016. The purpose of this study is to provide an overview of drought intensity for the last 36 years, analysing their severity, frequency and duration, considering hydro‐meteorological and agricultural aspects. To evaluate these two aspects, the 12‐month standardized precipitation index and the vegetation health index were considered to investigate drought characteristics. The definition of drought event for both these indices was performed regarding start and end month. In this context, drought duration is considered equal to the number of months of event, drought frequency is the number of events per time period and the drought severity is the absolute value of integral area below zero. Results show that the most severe and prolonged drought occurred in 2011–2016. In a clear contrast to previous droughts in past decades, during these last 5‐years period drought were more frequent, severe and affected a larger area with significant impacts for population, as well as economical activities.

Ureaplasma parvum causes hyperammonemia in a pharmacologically immunocompromised murine model - X. Wang; K. E. Greenwood-Quaintance; M. J. Karau; D. R. Block; J. N. Mandrekar; S. A. Cunningham; J. M. Mallea; R. Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Interaction rewiring and the rapid turnover of plant–pollinator networks - Paul J. CaraDonna; William K. Petry; Ross M. Brennan; James L. Cunningham; Judith L. Bronstein; Nickolas M. Waser; Nathan J. Sanders (Ecology Letters, 2017)
Whether species interactions are static or change over time has wide‐reaching ecological and evolutionary consequences. However, species interaction networks are typically constructed from temporally aggregated interaction data, thereby implicitly assuming that interactions are fixed. This approach has advanced our understanding of communities, but it obscures the timescale at which interactions form (or dissolve) and the drivers and consequences of such dynamics. We address this knowledge gap by quantifying the within‐season turnover of plant–pollinator interactions from weekly censuses across 3 years in a subalpine ecosystem. Week‐to‐week turnover of interactions (1) was high, (2) followed a consistent seasonal progression in all years of study and (3) was dominated by interaction rewiring (the reassembly of interactions among species). Simulation models revealed that species’ phenologies and relative abundances constrained both total interaction turnover and rewiring. Our findings reveal the diversity of species interactions that may be missed when the temporal dynamics of networks are ignored.

Clinostomum album n. sp. and Clinostomum marginatum (Rudolphi, 1819), parasites of the great egret Ardea alba L. from Mississippi, USA - Thomas G. Rosser; Neely R. Alberson; Ethan T. Woodyard; Fred L. Cunningham; Linda M. Pote; Matt J. Griffin (Systematic Parasitology, 2017)

An experimental test of relatedness-based mate discrimination in a social lizard - Genevieve Bordogna; George Cunningham; Luisa J. Fitzpatrick; Ben Halliwell; Hannah E. A. MacGregor; Kirke L. Munch; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Ecological and socio-economic factors affecting extinction risk in parrots - George Olah; Stuart H. M. Butchart; Andy Symes; Iliana Medina Guzmán; Ross Cunningham; Donald J. Brightsmith; Robert Heinsohn (Biodiversity and Conservation, 2016)

Reforestation with native mixed‐species plantings in a temperate continental climate effectively sequesters and stabilizes carbon within decades - Shaun C. Cunningham; Timothy R. Cavagnaro; Ralph Mac Nally; Keryn I. Paul; Patrick J. Baker; Jason Beringer; James R. Thomson; Ross M. Thompson (Global Change Biology, 2015)
Reforestation has large potential for mitigating climate change through carbon sequestration. Native mixed‐species plantings have a higher potential to reverse biodiversity loss than do plantations of production species, but there are few data on their capacity to store carbon. A chronosequence (5–45 years) of 36 native mixed‐species plantings, paired with adjacent pastures, was measured to investigate changes to stocks among C pools following reforestation of agricultural land in the medium rainfall zone (400–800 mm yr −1 ) of temperate Australia. These mixed‐species plantings accumulated 3.09 ± 0.85 t C ha −1 yr −1 in aboveground biomass and 0.18 ± 0.05 t C ha −1 yr −1 in plant litter, reaching amounts comparable to those measured in remnant woodlands by 20 years and 36 years after reforestation respectively. Soil C was slower to increase, with increases seen only after 45 years, at which time stocks had not reached the amounts found in remnant woodlands. The amount of trees (tree density and basal area) was positively associated with the accumulation of carbon in aboveground biomass and litter. In contrast, changes to soil C were most strongly related to the productivity of the location (a forest productivity index and soil N content in the adjacent pasture). At 30 years, native mixed‐species plantings had increased the stability of soil C stocks, with higher amounts of recalcitrant C and higher C : N ratios than their adjacent pastures. Reforestation with native mixed‐species plantings did not significantly change the availability of macronutrients (N, K, Ca, Mg, P, and S) or micronutrients (Fe, B, Mn, Zn, and Cu), content of plant toxins (Al, Si), acidity, or salinity (Na, electrical conductivity) in the soil. In this medium rainfall area, native mixed‐species plantings provided comparable rates of C sequestration to local production species, with the probable additional benefit of providing better quality habitat for native biota. These results demonstrate that reforestation using native mixed‐species plantings is an effective alternative for carbon sequestration to standard monocultures of production species in medium rainfall areas of temperate continental climates, where they can effectively store C, convert C into stable pools and provide greater benefits for biodiversity.

Does morphology predict trophic position and habitat use of ant species and assemblages? - H. Gibb; J. Stoklosa; D. I. Warton; A. M. Brown; N. R. Andrew; S. A. Cunningham (Oecologia, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Endotoxin-induced HIF-1α stabilisation in equine endothelial cells: synergistic action with hypoxia - A. C. Brooks; N. Menzies-Gow; S. R. Bailey; F. M. Cunningham; J. Elliott (Inflammation Research, 2010)

The contribution of eastern-boundary density variations to the Atlantic meridional overturning circulation at 26.5° N - M. P. Chidichimo; T. Kanzow; S. A. Cunningham; W. E. Johns; J. Marotzke (Ocean Science, 2010)
We study the contribution of eastern-boundary density variations to sub-seasonal and seasonal anomalies of the strength and vertical structure of the Atlantic Meridional Overturning Circulation (AMOC) at 26.5° N, by means of the RAPID/MOCHA mooring array between April 2004 and October 2007. The major density anomalies are found in the upper 500 m, and they are often coherent down to 1400 m. The densities have 13-day fluctuations that are apparent down to 3500 m. The two strategies for measuring eastern-boundary density – a tall offshore mooring (EB1) and an array of moorings on the continental slope (EBH) – show little correspondence in terms of amplitude, vertical structure, and frequency distribution of the resulting basin-wide integrated transport fluctuations, implying that there are significant transport contributions between EB1 and EBH. Contrary to the original planning, measurements from EB1 cannot serve as backup or replacement for EBH: density needs to be measured directly at the continental slope to compute the full-basin density gradient. Fluctuations in density at EBH generate transport variability of 2 Sv rms in the AMOC, while the overall AMOC variability is 4.8 Sv rms. There is a pronounced deep-reaching seasonal cycle in density at the eastern boundary, which is apparent between 100 m and 1400 m, with maximum positive anomalies in spring and maximum negative anomalies in autumn. These changes drive anomalous southward upper mid-ocean flow in spring, implying maximum reduction of the AMOC, and vice-versa in autumn. The amplitude of the seasonal cycle of the AMOC arising from the eastern-boundary densities is 5.2 Sv peak-to-peak, dominating the 6.7 Sv peak-to-peak seasonal cycle of the total AMOC. Our analysis suggests that the seasonal cycle in density may be forced by the strong near-coastal seasonal cycle in wind stress curl.

A Robust Technique for Mapping Vegetation Condition Across a Major River System - S. C. Cunningham; R. Mac Nally; J. Read; P. J. Baker; M. White; J. R. Thomson; P. Griffioen (Ecosystems, 2009)

A six-year study of fire-related flowering cues and coexistence of two perennial grasses in a wet longleaf pine (Pinus palustris) savanna - J. Stephen Brewer; Amy L. Cunningham; Timothy P. Moore; Randell M. Brooks; Joanne L. Waldrup (Plant Ecology, 2009)

Patterns in the distribution of myctophid fish in the northern Scotia Sea ecosystem - Martin A. Collins; Jose C. Xavier; Nadine M. Johnston; Anthony W. North; Peter Enderlein; Geraint A. Tarling; Claire M. Waluda; Elizabeth J. Hawker; Nathan J. Cunningham (Polar Biology, 2008)

A cDNA Microarray for Crassostrea virginica and C. gigas - Matthew J. Jenny; Robert W. Chapman; Annalaura Mancia; Yian A. Chen; David J. McKillen; Hal Trent; Paul Lang; Jean-Michel Escoubas; Evelyne Bachere; Viviane Boulo; Z. John Liu; Paul S. Gross; et al. (Marine Biotechnology, 2007)

Levels of intra-host and temporal sequence variation in a large CO1 sub-units from Anisakis simplex sensu stricto (Rudolphi 1809) (Nematoda: Anisakisdae): implications for fisheries management - M. A. Cross; C. Collins; N. Campbell; P. C. Watts; J. C. Chubb; C. O. Cunningham; E. M. C. Hatfield; K. MacKenzie (Marine Biology, 2007)

Endotoxin-induced activation of equine platelets: evidence for direct activation of p38 MAPK pathways and vasoactive mediator production - A. C. Brooks; N. J. Menzies-Gow; C. Wheeler-Jones; S. R. Bailey; F. M. Cunningham; J. Elliott (Inflammation Research, 2007)

Nearshore fish ( Pholis gunnellus ) persists across the North Atlantic through multiple glacial episodes - M. J. HICKERSON; C. W. CUNNINGHAM (Molecular Ecology, 2006)
The intertidal biota of the North Atlantic is characterized by two disjunct communities (North American and European) exposed to different climatic regimes during the Pleistocene and in the Holocene. We collect multilocus DNA sequence data from the nearshore fish Pholis gunnellus to help uncover processes determining biogeographical persistence during periodic coastal glaciations. Coalescent‐based estimates from the multilocus DNA sequence data suggest that P. gunnellus persisted on both sides of the North Atlantic throughout the last two glacial maxima (> 202 000 years) with little trans‐Atlantic gene flow since divergence, very little structure among populations within Europe (Φ ST ST = 0.0–0.21). Although the ecological flexibility and high local migration of P. gunnellus could have enhanced this species’ survival across the Atlantic, logistic regression did not find a significant determinant of trans‐Atlantic persistence when considering 12 other North Atlantic phylogeographical studies from the literature.

New Resources for Marine Genomics: Bacterial Artificial Chromosome Libraries for the Eastern and Pacific Oysters (Crassostrea virginica and C. gigas) - Charles Cunningham; Jun-ichi Hikima; Matthew J. Jenny; Robert W. Chapman; Guang-Chen Fang; Chris Saski; Mats L. Lundqvist; Rod A. Wing; Pauline M. Cupit; Paul S. Gross; Greg W. Warr; Jeff P. Tomkins (Marine Biotechnology, 2006)

Characterisation of the European Marine Sites in South West England: The Fal and Helford Candidate Special Area of Conservation (cSAC) - W. J. Langston; B. S. Chesman; G. R. Burt; M. Taylor; R. Covey; N. Cunningham; P. Jonas; S. J. Hawkins (Hydrobiologia, 2006)

Phosphate nutrition effects on growth, phosphate transporter transcript levels and physiology of alfalfa cells - S. F. Abu. Qamar; T. G. Sors; S. M. Cunningham; B. C. Joern; J. J. Volenec (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Discrepancy Between Antennal and Behavioral Responses for Enantiomers of α-Pinene: Electrophysiology and Behavior of Helicoverpa armigera (Lepidoptera) - C. D. Hull; J. P. Cunningham; C. J. Moore; M. P. Zalucki; B. W. Cribb (Journal of Chemical Ecology, 2004)

Vulnerability of mouse cortical neurons to doxorubicin-induced apoptosis is strain-dependent and is correlated with mRNAs encoding Fas, Fas-Ligand, and metalloproteinases - M. Wetzel; J. Tibbitts; G. A. Rosenberg; L. A. Cunningham (Apoptosis, 2004)

Effects of dopamine D 1 - or D 2 -like receptor antagonists on the hypermotive and discriminative stimulus effects of (+)-MDMA - Marcy J. Bubar; Kami M. Pack; Paul S. Frankel; Kathryn A. Cunningham (Psychopharmacology, 2004)

Antioxidant enzyme activity and mRNA expression in the islets of Langerhans from the BB/S rat model of type 1 diabetes and an insulin-producing cell line - Louise A. Sigfrid; James M. Cunningham; Neil Beeharry; L. A. Hkan Borg; Alma L. Rosales Hernandez; Carina Carlsson; Adrian J. Bone; Irene C. Green (Journal of Molecular Medicine, 2004)

The sodium channel blocker RS100642 reverses down-regulation of the sodium channel α-subunit Nav 1.1 expression caused by transient ischemic brain injury in rats - C. Yao; A. J. Williams; X. -C. M. Lu; R. A. Price; B. S. Cunningham; R. Berti; F. C. Tortella; J. R. Dave (Neurotoxicity Research, 2003)

Diminished energy metabolism and enhanced apoptosis in livers of B6C3F1 mice treated with the antihepatocarcinogen rotenone - C. Wang; J. Youssef; B. Saran; P.G. Rothberg; M.L. Cunningham; A. Molteni; M. Badr (Molecular and Cellular Biochemistry, 1999)

Genetic differences in cocaine-induced conditioned place preference in mice depend on conditioning trial duration - Christopher L. Cunningham; Shelly D. Dickinson; Nicholas J. Grahame; Dobrina M. Okorn; Carrie S. McMullin (Psychopharmacology, 1999)

Insulitis and mechanisms of disease resistance: studies in an animal model of insulin dependent diabetes mellitus - A. J. Bone; P. R. Hitchcock; D. J. Gwilliam; J. M. Cunningham; J. Barley (Journal of Molecular Medicine, 1999)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

Comparative phylogeography and the history of endemic vertebrates in the Wet Tropics rainforests of Australia - C. J. SCHNEIDER; M. CUNNINGHAM; C. MORITZ (Molecular Ecology, 1998)
We examine the effects of historical climate change on vertebrate differentiation in tropical rainforest by comparing phylogeographic patterns in six species of widespread rainforest‐restricted herpetofauna from throughout the Wet Tropics of Australia. Qualitative and quantitative comparisons of phylogeographic structure reveal strikingly similar patterns of pre‐Pleistocene vicariant population differentiation on either side of a previously identified biogeographic break (variously referred to as the Black Mountain Barrier or Corridor; BMC). While divergence across the BMC antedates the Pleistocene, the impact of Quaternary climate change is apparent in populations on either side of the BMC. Consistent with palaeoclimatological reconstructions for the region, the distribution and degree of mtDNA diversity suggests that populations were fragmented and reduced to multiple refugia during Pleistocene glacial periods, with expansion following Holocene rainforest recovery. This pattern is repeated on both sides of the BMC, but substantial differences in the amount and distribution of mtDNA diversity within species indicate the importance of species‐specific ecological characteristics. The historical processes of extinction and (re)colonization revealed by the comparative phylogeographic analysis of mtDNA sequences substantiate earlier suggestions that current regional patterns of species distribution and diversity in the Wet Tropics are largely determined by local extinctions and subsequent recolonization driven by Quaternary climate changes.

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Portage: A new early-maturing, round white table potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1995)

Prestile: A new round white potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1994)

Inheritance of resistance to Verticillium wilt in Wisconsin - D. E. Hunter; H. M. Darling; F. J. Stevenson; C. E. Cunningham (American Journal of Potato Research, 1968)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

Reducing sugar content of maine-grown potatoes treated with maleic hydrazide - M. E. Highlands; J. J. Licciardello; C. E. Cunningham (American Journal of Potato Research, 1952)